2014
DOI: 10.1016/j.diii.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging of peritoneal carcinomatosis and its mimics

Abstract: Invasive peritoneal disease includes more than just peritoneal carcinomatosis. Although this is the most common aetiology, especially when a primary is found, other conditions may be responsible for peritoneal invasion. A rigorous analysis of CT features taken together with the clinical and biological context usually allows the main differential diagnoses, which entail different types of management, to be drawn out. Pseudomyxoma peritonei, peritoneal lymphomatosis, tuberculosis, peritoneal mesothelioma, diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 28 publications
3
108
0
4
Order By: Relevance
“…This is strictly consistent with data from previous studies in which the fat halo sign is observed in 65-85% of MP cases [18,[21][22][23][24]. Although not always observed, the fat halo sign is critical for confirming the diagnosis of MP because it is never observed in other diseases of the mesentery with infiltration and/or tumoral involvement which do not spare the regions surrounding vessels [13,15,17,25,26].…”
Section: Discussionsupporting
confidence: 92%
“…This is strictly consistent with data from previous studies in which the fat halo sign is observed in 65-85% of MP cases [18,[21][22][23][24]. Although not always observed, the fat halo sign is critical for confirming the diagnosis of MP because it is never observed in other diseases of the mesentery with infiltration and/or tumoral involvement which do not spare the regions surrounding vessels [13,15,17,25,26].…”
Section: Discussionsupporting
confidence: 92%
“…The lower small bowel mesentery near the terminal ileum is one of the natural sites where tumor initially deposits. Therefore, the terminal ileum is a critical area to evaluate when searching for evidence of peritoneal metastases (8). Different from malignancies, the omental involvement is uncommon in acute peritonitis whereas the small bowel mesentery can be frequently involved.…”
Section: Main Pointsmentioning
confidence: 99%
“…On imaging, if a mesenteric mass is identified, this must lead to a consideration of the differential diagnoses, distinguishing the fluid lesions, consisting of cystic lymphangioma and mesothelial lesions, from solid masses including desmoid tumour, solitary fibrous tumour, peritoneal carcinosis, and leiomymomatosis, and also from fat-containing lesions such as teratoma and lipoma [12,13]. In our patient, the lesion was purely solid with no cystic or fatty component.…”
Section: Discussionmentioning
confidence: 89%